الشاعر الغيني محمد الأمين جابي حياته وشعره : دراسة وصفية تحليلية - موسى، كمارا محمد (Kulliyah of Islamic Revealed Knowledge and Human Sciences, International Islamic University Malaysia, 2018)
This study aims to critically analyse the poetry of Guinean poet, Mohamed Lamine Diaby. His poetry has not been studied in detail before, despite the richness in its various intellectual dimensions, poetic purposes and its distinctive poetic experience. The study elaborates the life of the poet and his scientific efforts, and explores the content of his poetry that relates to human life and religion. The research critically analyses the poet's intellectual, political, national, social and religious dimensions. This is followed by a discussion of the poetic experience, the meanings and ideas, language and style, image and imagination, emotion and feeling, and construction of external and internal rhythm of the poems. The researcher used the inductive, descriptive and analytical methods to achieve the objectives of the study. The results of this study yield the richness of the ideas contained in the poetry of Mohamed Lamine Diaby, and its importance in dealing with human issues, life and religion, including issues of the Islamic nation and diversity in the maturity of the poetic experience.